Biphasic Effect of Profilin Impacts the Formin mDia1 Force-Sensing Mechanism in Actin Polymerization - Kubota, Hiroaki (Biophys J, 2017)
Formins are force-sensing proteins that regulate actin polymerization dynamics. Here, we applied stretching tension to individual actin filaments under the regulation of formin mDia1 to investigate the mechanical responses in actin polymerization dynamics. We found that the elongation of an actin filament was accelerated to a greater degree by stretching tension for ADP-G-actin than that for ATP-G-actin. An apparent decrease in the critical concentration of G-actin was observed, especially in ADP-G-actin. These results on two types of G-actin were reproduced by a simple kinetic model, assuming the rapid equilibrium between pre- and posttranslocated states of the formin homology domain two dimer. In addition, profilin concentration dramatically altered the force-dependent acceleration of actin filament elongation, which ranged from twofold to an all-or-none response. Even under conditions in which actin depolymerization occurred, applications of a several-piconewton stretching tension triggered rapid actin filament elongation. This extremely high force-sensing mechanism of mDia1 and profilin could be explained by the force-dependent coordination of the biphasic effect of profilin; i.e., an acceleration effect masked by a depolymerization effect became dominant under stretching tension, negating the latter to rapidly enhance the elongation rate. Our findings demonstrate that the biphasic effect of profilin is controlled by mechanical force, thus expanding the function of mDia1 as a mechanosensitive regulator of actin polymerization.